Mr. Mallock as Statistician and British Income Statistics - Young, Allyn A.; Mallock, W.H. (Quarterly Journal of Economics, 1911)
Journal Article Mr. Mallock as Statistician and British Income Statistics Get access Allyn A. Young Allyn A. Young Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 25, Issue 2, February 1911, Pages 376–386, https://doi.org/10.2307/1884954 Published: 01 February 1911